Assessing the «Assistance at Home» projects through the employee's perspectives - Κανδυλάκη, Αγάπη; Τσαϊρίδης, Χαράλαμπος (The Greek Review of Social Research, 2016)
«Assistance at Home» could be considered as a unit of inclusive primary health and social care to the elderly and the disabled. Especially in the new Kapodistrian Municipalities, the unit operates as a social services as well. This article presents an evaluation study of the 'Assistance at Home' Project in three Prefectures in Greece (Eastern Macedonia and Thrace, Achaia in Western Greece and Region of Heraklion in Crete, through the perspective of the people who work in the project. The research took place in a climate of anxiety and uncertainty regarding the survival of the project.